Robust cyclical growth - Anjan Mukherji (Osaka University, Institute of Social and Economic Research (ISER), 2003)
The stability of cyclical growth within the context of a model in Matsuyama (1999) is examined. It is shown that but for an extreme situation, the two-cycles are unique and a range of parameter values which imply the stability of such cyclical growth is derived. The growth enhancing property of 2-cycles are shown to be retained by any cycle; the results of simulation exercises carried out are reported to show that for very wide range of parameter values, such cyclical growth paths are stable and thus robustness of the conclusions are established. Finally, the configuration of parameters for which the dynamics exhibits complicated (chaotic) behavior is also identified.
Keywords: 330; cycles; stability of cycles; robustness; growth; innovation; chaos; Neue Wachstumstheorie; Innovation; Investition; Wachstumszyklus; Simulation; Robustes Verfahren